On Contra I_g-continuity in Ideal Topological Spaces - Rajamani, M.; Inthumathi, V.; Chitra, V. (Journal of Informatics and Mathematical Sciences, 2011)
In this paper, I_g-closed sets and I_g-open sets are used to define and investigate a new class of functions called contra I_g-continuous functions in ideal topological spaces. We discuss the relationships with some other related functions.